x → ∞ lim ( x + x − x ) , x → ∞ lim ⎝ ⎛ x + x + x − x ⎠ ⎞
It is possible to show that both the limits above are equal to 2 1 .
Is it true that the limit below is also equal to 2 1 ?
x → ∞ lim ⎝ ⎛ x + x + x + x − x ⎠ ⎞
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Kudos. You tamed the beast quite elegantly.
If you use series expansions of these radicals then each of them starts with 1/2 followed by other terms which -> 0 as x -> infinity
Problem Loading...
Note Loading...
Set Loading...
The fact is, for any positive integer n larger than 2, we have x → ∞ lim ⎝ ⎜ ⎛ n x + x + x + . . . x − x ⎠ ⎟ ⎞ = 2 1 . Before proving this limit, we need the following lemma.
Lemma. For any real number a > 0 , there exists a real number x such that if N ≥ x , then N + a > a .
Proof. This follows from the fact that x + a is a strictly increasing function.
With that in mind, we can proceed with the evaluation of the limit. We first consider the case when n tends to infinity. Then, we have u u 2 − u − x u : = = = = x + x + x + . . . x + u 0 2 1 + 1 + 4 x since u > 0 . Thus, the limit evaluates to x → ∞ lim ( u − x ) = = = = x → ∞ lim ( 2 1 + 1 + 4 x − x ) x → ∞ lim ( 2 1 + 1 + 4 x − 2 x ) x → ∞ lim ( 2 1 + 1 + 4 x − 4 x ) 2 1 . Now, using the lemma above, we know that for any positive integer n , the following inequality holds for x > 0 . u ≥ n x + x + x + . . . x ≥ x + x . Hence, the result follows directly from squeeze theorem.